A Engorda dos Capadetes: Typo para carne (typo exportaÃ§Ã£o, â€œBacon typeâ€) - Athanassof, Nicolau (REVISTA DE AGRICULTURA, 2019)
A Engorda dos Capadetes: Typo para carne (typo exportaÃ§Ã£o, â€œBacon typeâ€)